Integrated variable-viscosity polymer thickening agent and preparation method thereof
By designing a variable viscosity polymer thickening agent containing specific monomers and polymerization processes, the existing thickening agents have poor temperature resistance, low shear resistance and high friction resistance in application scenarios are solved, and the existing thickening agents have been achieved. Improve the performance of thickeners and expand their application scope.
Patent Information
- Application Number
- CN202411660175.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-20
AI Technical Summary
In the application scenarios, existing thickeners have problems such as many residues, poor temperature resistance, low shear resistance and high friction resistance, which are difficult to meet the needs of complex formation transformation.
The integrated viscous polymer thickening agent is used, and the raw material components include acrylamide, N-benzyl-N-methacryloyloxy-N,N-dimethylammonium chloride, dodecyl poly Oxyethylene ether methacrylate, azobiisobutymidine hydrochloride and solvents form a reversible physical crosslinking network through carefully designed monomer ratios and unique polymerization processes.
It significantly improves the apparent viscosity, temperature and shear resistance of the thickener, and has excellent effects in anti-swelling, resistance reduction, salt resistance and suspended sand, meeting the needs of complex formation transformation.
Smart Images

Figure CN119409906A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of oilfield chemicals, in particular to an integrated variable viscosity polymer thickener and a preparation method thereof. Background Art
[0002] With the continuous growth of global demand for oil and gas resources, oil and gas exploration and development technologies are constantly improving to meet the challenge of the decreasing high-porosity, high-permeability, high-quality oil and gas resources. In the long-term exploitation process, most high-quality oil and gas fields have gradually entered the late stage of exploitation. Therefore, the development of unconventional oil and gas reservoirs has become the current focus. This type of reservoir often has a complex formation environment and poor permeability, which puts higher requirements on exploration and development technology. In order to improve the permeability of the formation and increase oil and gas production, it is particularly important to effectively transform the formation. Among them, hydraulic fracturing, as an important means of transforming low-permeability reservoirs, has received widespread attention.
[0003] Hydraulic fracturing technology uses the high pressure generated by the fracturing truck to inject highly viscous liquid into the bottom of the well, causing the formation to break and form new cracks. These cracks are effectively supported by proppants, which significantly improves the permeability of the formation, making it easier for oil and gas to penetrate into the wellbore through the cracks, effectively increasing oil well production and reservoir utilization. In this process, fracturing fluid is a key link, which is mainly responsible for creating cracks and transporting proppants, and its performance has a decisive influence on the fracturing effect.
[0004] Fracturing fluids are mainly divided into three categories: water-based, oil-based and foam-based. Water-based fracturing fluids are widely used in major oil fields due to their high safety, low cost and simple process. In water-based fracturing fluids, thickeners are the main agent and play a decisive role in the performance of the fracturing fluid system.
[0005] However, the thickeners in the prior art still have many deficiencies in application scenarios. The natural plant gum fracturing fluid system has a lot of residues after breaking the gel, which causes great damage to the physical properties of the original formation; although the clean fracturing fluid system has no residue after breaking the gel, its temperature resistance is poor and it is expensive, which limits its application; although the polymer fracturing fluid system can be obtained by chemical crosslinking or physical crosslinking, the chemical crosslinking method will reduce the shear resistance of the system, and the friction resistance is high during the pumping process, affecting the construction effect. In contrast, although the supramolecular hydrophobic associating polymer fracturing fluid system obtained by physical crosslinking has excellent shear recovery performance and viscoelastic properties, and the residue content after breaking the gel is low, it still needs further research and development to optimize its performance and meet a wider range of fracturing construction needs.
[0006] In summary, although the thickeners in the prior art have certain advantages in application scenarios, they still have many disadvantages and shortcomings, such as a lot of residue, poor temperature resistance, low shear resistance and high friction. It is urgent to develop new thickeners to overcome the above defects. Summary of the invention
[0007] The object of the present invention is to provide an integrated variable viscosity polymer thickener and a preparation method thereof. To achieve the above object, the technical solution of the present invention is: The present invention provides an integrated variable viscosity polymer thickener, the raw material components of the thickener include: Acrylamide (AM), N-benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride (MTC), behenyl polyoxyethylene ether methacrylate (BEM), azobisisobutyramidine hydrochloride, solvent.
[0008] The raw materials are calculated by mass as follows: Acrylamide (AM): 3~10 parts; N-Benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride (MTC): 0.5~1 part; Behenyl polyoxyethylene ether methacrylate (BEM): 0.5~1 part; Azobisisobutylamidine hydrochloride (V50): 0.05~0.3 parts; Solvent: 60~90 parts.
[0009] The solvent is deionized water.
[0010] A method for preparing an integrated variable viscosity polymer thickener, the method comprising the following steps: Step 1, weigh the raw materials: acrylamide, N-benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride, behenyl polyoxyethylene ether methacrylate, azobisisobutyramidine hydrochloride, and solvent; Step 2: Evenly mix acrylamide, N-benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride and behenyl polyoxyethylene ether methacrylate in a solvent, pour into a reaction kettle, introduce nitrogen, and slowly heat after half an hour; Step 3: After the above reaction is stable, azobisisobutylamidine hydrochloride is uniformly added to the above reaction solution as an initiator, the reaction temperature is controlled, and the reaction is continued for 4 to 9 hours after the titration to obtain a colorless transparent colloid; Step 4: Wash the colorless and transparent colloid with anhydrous ethanol, cut into pieces, and dry to obtain a white powder, which is a thickener.
[0011] In step 1, the weight fractions of each raw material are as described above.
[0012] In step 3, the reaction temperature is 45-75°C.
[0013] Compared with the prior art, the present invention has the following beneficial effects: 1. The integrated variable viscosity polymer thickener of the present invention has achieved significant performance improvement and wide expansion of application scope through carefully designed monomer ratios and unique polymerization processes. The thickener not only greatly improves the apparent viscosity, but also significantly enhances the temperature and shear resistance, while showing excellent performance in anti-swelling, drag reduction, salt resistance and suspended sand. These performance improvements are due to the introduction of N-benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride (MTC) and behenyl polyoxyethylene ether methacrylate (BEM) monomers, which significantly optimize the microstructure and macroscopic properties of the thickener by forming a reversible physical cross-linking network and enhancing intermolecular forces.
[0014] 2. The thickener of the present invention utilizes the reversible physical cross-linked network formed by the hydrophobic associating polymer in water to effectively increase the fluid dynamics volume and solution viscosity. At the same time, the addition of BEM not only enhances the interaction forces such as hydrogen bonds, hydrophobic associations and linear entanglements between polymer molecules, but also significantly improves the water solubility of the thickener, making it easier to disperse and dissolve in water. These mechanistic advantages together contribute to the significant improvement in the performance of the thickener.
[0015] 3. The thickener of the present invention also brings significant social benefits. By improving production efficiency and product quality, reducing production costs and environmental pollution, it has made positive contributions to the sustainable development of society. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the infrared spectrum of the thickener prepared in Example 1.
[0017] Figure 2 This is the temperature and shear resistance diagram of the thickener prepared in Example 1.
[0018] Figure 3 This is the drag reduction diagram of the thickener prepared in Example 1. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The invention discloses an integrated variable viscosity polymer thickener and a preparation method thereof.
[0021] 1. The raw materials include: Acrylamide (AM) is the most important and simplest type of acrylamide. It has a wide range of uses and is used as a raw material for organic synthesis and a raw material for polymer materials. Its polymer is soluble in water, so it is used to produce flocculants for water treatment, especially for the flocculation of proteins and starch in water. In addition to flocculation, it also has excellent properties such as thickening, shear resistance, drag reduction, and dispersibility. When used as a soil conditioner, it can increase the water permeability and moisture retention of the soil; when used as a paper filler auxiliary, it can increase the strength of the paper to replace starch and water-soluble ammonia resin; when used as a chemical grouting agent, it is used for tunnel excavation, oil well drilling, mines and dams in civil engineering projects; when used as a fiber modifier, it can improve the physical properties of synthetic fibers; when used as a preservative, it can be used for the anti-corrosion of underground components; it can also be used as an additive in the food industry, a dispersant for pigments, and a printing and dyeing paste. When combined with a phenolic resin solution, it can be made into an adhesive for glass fibers, and when combined with rubber, it can be made into a pressure-sensitive adhesive. It can be polymerized with monomers such as vinyl acetate, styrene, vinyl chloride, acrylonitrile, etc. to prepare many synthetic materials. This product can also be used as a raw material for medicine, pesticides, dyes, and coatings.
[0022] N-Benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride (MTC) is an organic compound. Due to the presence of double bonds and cationic quaternary ammonium groups in the molecule, it can be copolymerized with many unsaturated monomers. The copolymer carries a positive charge in its aqueous solution to generate cationic or zwitterionic polymers, which are important raw materials for oilfield chemicals. Since the copolymer has good hydrolysis stability and temperature and salt resistance, the copolymer of this product and other monomers can be used for temperature and salt resistant drilling fluid treatment agents, oil well cement admixtures, acid fracturing additives and oil displacement agents.
[0023] In order to achieve the dual purpose of improving the crosslinking strength and solubility of the integrated variable viscosity polymer thickener, behenyl polyoxyethylene ether methacrylate (BEM) is used. The polyether formed by the condensation of polyethylene glycol and stearyl alcohol has the characteristics of high stability, good water solubility, electrolyte resistance, easy biodegradation, small foam, high surface activity, etc. It is widely used in the washing industry, textile industry, papermaking industry, agriculture, oil field industry, etc. Straight-chain alkanes are highly hydrophobic. The more oxygen on the hydrophilic group of the molecule, the easier it is to form more hydrogen bonds with water, and the better the water solubility. Due to the presence of alkane chains in behenyl polyoxyethylene ether methacrylate, in aqueous solution, the hydrophobic part aggregates and associates through non-covalent bonds to form a surfactant micelle structure. Therefore, the functional monomer has the following characteristics: (1) specific active acrylate groups with high polymerization activity; (2) embedded oxyethylene chain segments increase the water solubility of BEM monomers; (3) C22 straight-chain alkanes are easy to form aggregates in water and show strong associative ability. It is expected to be used in the application field of developing high relative molecular weight cationic polymer products with temperature resistance, pressure resistance, acid, alkali resistance and salt resistance.
[0024] Azobisisobutylamidine hydrochloride (V50) does not induce decomposition and the decomposition reaction is first-order. After changing the pH in the solution, it will cause slight decomposition. It can be used alone to initiate polymerization at a relatively low temperature, only a very low concentration is required, and there is very little catalyst residue. The polymerization proceeds at a constant rate and is almost 100% complete without changing the pH. It can produce polymers with ultra-high molecular weight and high-quality water solubility, and the product color is slight. It is stored at room temperature and is relatively stable. The price-performance ratio is slightly higher, but the dosage is small and the effect is good.
[0025] The solvent, deionized water, was homemade in the laboratory.
[0026] 2. Mass ratio between components Acrylamide (AM): 3~10 parts; N-Benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride (MTC): 0.5~1 part; Behenyl polyoxyethylene ether methacrylate (BEM): 0.5~1 part; Azobisisobutylamidine hydrochloride (V50): 0.05~0.3 parts; Solvent: deionized water: 60~90 parts.
[0027] A method for preparing an integrated variable viscosity polymer thickener, the method comprising the following steps: S1. Weigh the raw materials according to the formula: acrylamide (AM): 3-10 parts; N-benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride (MTC): 0.5-1 parts; behenyl polyoxyethylene ether methacrylate (BEM): 0.5-1 parts; azobisisobutyramidine hydrochloride (V50): 0.05-0.3 parts; solvent deionized water: 60-90 parts; S2. The prepared acrylamide, N-benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride and behenyl polyoxyethylene ether methacrylate were mixed in deionized water, poured into a reaction vessel, introduced nitrogen, and slowly heated after half an hour; S3. After the above reaction is stable, 0.05-0.3 parts of azobisisobutylamidine hydrochloride as an initiator is uniformly added to the above reaction solution, and the reaction temperature is controlled at 45-75°C. After the titration, the reaction is continued for 4-9 hours to obtain a colorless transparent colloid.
[0028] S4. The colorless transparent colloid is washed with anhydrous ethanol, chopped and dried to obtain a white powder, which is the target thickener of the present invention.
[0029] The thickener provided by the present invention has the following mechanism: (1) Compared with HPAM, the hydrophobic associative polymer with branches (a small amount of hydrophobic groups in the polymer skeleton) can quickly form a reversible physical cross-linked network in water, showing more complex rheological properties and response to external stimuli. They have great application potential in drug delivery, shape memory materials, drag reducers, thickeners for oil field hydraulic fracturing, etc. The intermolecular force of the hydrophobic group increases with the increase of the number of hydrophobic groups and the length of the hydrophobic carbon chain. The fluorescent probe method is often used to confirm the existence of the hydrophobic micro-region of the polymer. Hydrophobic monomers are generally difficult to dissolve in water. As the number of hydrophobic groups and the length of the hydrophobic carbon chain in the polymer increase, the solubility of the polymer will also decrease. Behenyl polyoxyethylene ether methacrylate has the characteristics of solubilization, reducing surface tension and spontaneous aggregation into associative micelles in water. By introducing dioctyl polyoxyethylene ether methacrylate into HPAM to synthesize an amphiphilic water-soluble polymer, the hydrophobic carbon chain C22 can form a reversible physical cross-linking network through association, increase the hydrodynamic volume of the polymer, and increase the viscosity of the polymer solution. The oxyethylene segment is a highly polar hydrophilic flexible segment, and the synthesized material usually has excellent flexibility, water retention, tensile strength, swelling and environmental stability. In this case, the thickener contains an active acrylate group, exhibits high polymerization activity, and is conducive to the synthesis of polymers with small size and multi-block sequence structure.
[0030] The present invention adopts aqueous solution free radical polymerization method to synthesize an amphiphilic functional monomer modified hydrophobic associating polymer thickener. The entanglement of polymer chains is the theoretical basis of polymer solution rheology. Different flexible segments in the polymer have different molecular structures and linear entanglement forms. With the increase of ethylene oxide chains, some intermolecular forces may be generated in the polymer aqueous solution, which are specifically manifested as follows: (1) the hydrogen bonds formed between water and amide groups will enhance the solubility of the polymer and the binding force between chains; (2) the hydrogen bonds between water and ethylene oxide segments will enhance the binding force between polymer chains; (3) C22 has strong hydrophobicity, and under the action of "entropy drive", hydrophobic associating micelles can be formed, and the intermolecular binding force increases; (4) the hydrophobicity of the hydrophobic chain is enhanced due to the repulsive effect between the hydrophobic chain and the hydrophilic ethylene oxide segment, and the hydrophobic associating strength increases; (5) due to the presence of hydrogen bonds, the hydrophobic associating structure increases the linear entanglement between the ethylene oxide segments. Therefore, with the increase of ethylene oxide chain segments, the interaction force between polymer molecules increases, the self-assembly behavior of polymers and the density of interpenetrating spatial network structure are enhanced, which has different effects on the macroscopic properties of polymers. Polymers can spontaneously aggregate in water through the "entropy-driven process" to form dynamic and reversible physical cross-linked association structures, increase the hydrodynamic volume of polymers, and form dense three-dimensional spatial network structures; (6) In polymer solutions, hydrophobic association, hydrogen bonding, van der Waals forces, etc. coexist synergistically, and hydrophobic association and linear entanglement cross-linked network structures exist between polymers at the same time. The strong staggered structure and high interfacial adhesion force make the polymer dissipate more energy during the external shear deformation process, and the polymer exhibits higher toughness and stability. With the increase of polymer concentration, the interaction force between polymers is enhanced, and the multi-bridge supramolecular structure formed by linear entanglement and hydrophobic association is enhanced. The polymer solution exhibits more complex fluid properties and response to external stimuli, making the polymer have higher environmental adaptability.
[0031] The present invention is described in detail below by way of examples: Example 1 1. Add 8 parts of acrylamide, 1 part of docosyl polyoxyethylene ether methacrylate, 1 part of N-benzyl-N-methacryloyloxy-N,N-dimethylamino ammonium chloride and 89.95 parts of deionized water to the reactor, and pass nitrogen for half an hour to remove oxygen. Then raise the temperature to 55°C, add 0.05 parts of initiator azobisisobutyramidine hydrochloride dropwise, react for 6 hours, and obtain a colorless transparent gel, which is the target thickener.
[0032] 2. Take 2g of the target thickener and dissolve it in 400g of experimental water. After it is fully dissolved, use a six-speed viscometer to measure its viscosity. The apparent viscosity of 0.5% of the mass fraction is 150mPa·s. It has a good thickening effect.
[0033] Example 2 1. Add 9 parts of acrylamide, 0.5 parts of behenyl polyoxyethylene ether methacrylate, 0.5 parts of N-benzyl-N-methacryloyloxy-N,N-dimethylamino ammonium chloride and 99.8 parts of deionized water to the reactor, and pass nitrogen for half an hour to remove oxygen. Then raise the temperature to 55°C, add 0.2 parts of initiator azobisisobutyramidine hydrochloride dropwise, react for 6 hours, and obtain a colorless transparent gel, which is the target thickener.
[0034] 2. Take 2g of the target thickener and dissolve it in 400g of experimental water. After it is fully dissolved, use a six-speed viscometer to measure its viscosity. The apparent viscosity of 0.5% of the mass fraction is 130mPa·s. It has a good thickening effect.
[0035] Example 3 1. Add 8 parts of acrylamide, 1 part of docosyl polyoxyethylene ether methacrylate, 1 part of N-benzyl-N-methacryloyloxy-N,N-dimethylamino ammonium chloride and 89.7 parts of deionized water to the reactor, and pass nitrogen for half an hour to remove oxygen. Then raise the temperature to 55°C, add 0.3 parts of initiator azobisisobutyramidine hydrochloride dropwise, react for 6 hours, and obtain a colorless transparent gel, which is the target thickener.
[0036] 2. Take 2g of the target thickener and dissolve it in 400g of experimental water. After it is fully dissolved, use a six-speed viscometer to measure its viscosity. The apparent viscosity of 0.5% of the mass fraction is 140mPa·s. It has a good thickening effect.
[0037] Figure 1 This is the infrared spectrum of the thickener prepared in Example 1.
[0038] from Figure 1 It can be seen that 3466 cm -1 and 3188 cm -1 The absorption peak of NH stretching vibration in acrylamide is at 2922 cm; the absorption peak of CH stretching vibration in the methylene group of hydrophobic monomer behenyl polyoxyethylene ether methacrylate is at 2922 cm -1 and 2860 cm -1 The C=O stretching vibration of the methylene group of behenyl polyoxyethylene ether methacrylate is at 1670 cm -1 There is an absorption peak; the rigid monomer N-benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride is at 1452 cm -1 There is an absorption peak on the benzene ring skeleton.
[0039] Compared with HPAM, the hydrophobic associating polymer in the present invention can quickly form a reversible physical cross-linked network in water. This network structure not only increases the hydrodynamic volume of the polymer, but also increases the viscosity of the polymer solution, so that the thickener exhibits more complex rheological properties and responsiveness to external stimuli in the application. In the thickener of the present invention, the embedding of BEM increases the oxyethylene chain segment, thereby enhancing the interaction force between polymer molecules. These forces include hydrogen bonds, hydrophobic associations and linear entanglements, which work synergistically to enable the polymer to spontaneously aggregate in water to form a dynamic, reversible physical cross-linked associative structure. This structure not only improves the stability and toughness of the polymer, but also enhances its environmental adaptability. The oxyethylene chain segment in BEM is a highly polar hydrophilic flexible chain segment, and its addition significantly improves the water solubility of the thickener. This makes the thickener easier to disperse and dissolve in water, thereby improving its efficiency and convenience of use.
[0040] The present invention successfully prepared an integrated variable viscosity polymer thickener by introducing two innovative monomers, N-benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride (MTC) and behenyl polyoxyethylene ether methacrylate (BEM). The thickener not only achieved significant improvement in performance, but also showed extensive potential and value in practical applications.
[0041] 1. Significantly improve the apparent viscosity: The thickener of the present invention significantly improves the apparent viscosity of the polymer through the synergistic effect of MTC and BEM. This enables the thickener to more effectively increase the viscosity of the liquid during application and meet the requirements of specific processes for high-viscosity liquids.
[0042] 2. Enhanced heat and shear resistance: Traditional thickeners tend to have reduced performance under high temperature or high shear conditions, but the present invention optimizes the monomer ratio and polymerization process to make the thickener perform well in terms of heat and shear resistance. This ensures the stability and durability of the thickener under high temperature or high shear conditions. Figure 2 The temperature and shear resistance of the thickener prepared in Example 1 is shown in Figure 1. The fixed shear rate is 170 s -1 When the temperature rises to 120 ℃, the apparent viscosity of the thickener HLCW aqueous solution with a mass fraction of 0.5% is 57.36 mPa·s. After shearing for 1.5 hours, the residual viscosity of the thickener HLCW aqueous solution is 78.96 mPa·s.
[0043] 3. Optimize the performance of anti-swelling, drag reduction, salt resistance and suspended sand: The thickener of the present invention shows excellent performance in anti-swelling, drag reduction, salt resistance and suspended sand. The improvement of these performances is due to the addition of MTC and BEM, which achieve effective control of liquid fluidity by improving the microstructure and intermolecular forces of the polymer. Figure 3This is the drag reduction diagram of the thickener prepared in Example 1. When the mass fraction of the thickener is 0.0125%, the drag reduction rate is 73.56%. When the concentration of the thickener gradually increases, the drag reduction effect decreases.
[0044] The above detailed description of the preferred embodiments of the present invention is only used to help understand the present invention and is not intended to limit the present invention. Any local modification or replacement within the technical scope disclosed by the present invention by anyone familiar with the technology should be included in the scope of the present invention.
Claims
1. An integrated variable viscosity polymer thickener, characterized in that: The raw material components of the thickener include: Acrylamide (AM), N-benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride (MTC), behenyl polyoxyethylene ether methacrylate (BEM), azobisisobutyramidine hydrochloride, solvent.
2. The integrated variable viscosity polymer thickener according to claim 1, characterized in that: The raw materials are calculated by mass as follows: Acrylamide (AM): 3~10 parts; N-Benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride (MTC): 0.5~1 part; Behenyl polyoxyethylene ether methacrylate (BEM): 0.5~1 part; Azobisisobutylamidine hydrochloride (V50): 0.05~0.3 parts; Solvent: 60~90 parts.
3. The integrated variable viscosity polymer thickener according to claim 1, characterized in that: The solvent is deionized water.
4. A method for preparing an integrated variable viscosity polymer thickener, characterized in that: The method includes the following steps: Step 1, weigh the raw materials: acrylamide, N-benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride, behenyl polyoxyethylene ether methacrylate, azobisisobutyramidine hydrochloride, and solvent; Step 2: Evenly mix acrylamide, N-benzyl-N-methacryloyloxy-N,N-dimethylaminoammonium chloride and behenyl polyoxyethylene ether methacrylate in a solvent, pour into a reaction kettle, introduce nitrogen, and slowly heat after half an hour; Step 3: After the above reaction is stable, azobisisobutylamidine hydrochloride is uniformly added to the above reaction solution as an initiator, the reaction temperature is controlled, and the reaction is continued for 4 to 9 hours after the titration to obtain a colorless transparent colloid; Step 4: Wash the colorless transparent colloid with anhydrous ethanol, cut into pieces, and dry to obtain a white powder, which is the thickener.
5. The method for preparing an integrated variable viscosity polymer thickener according to claim 4, characterized in that: In step 1, the mass fractions of each raw material are as described in claim 2.
6. The method for preparing an integrated variable viscosity polymer thickener according to claim 4, characterized in that: In step 3, the reaction temperature is 45-75°C.
Citation Information
Patent Citations
Temperature-resistant acid liquor thickening agent as well as preparation method and application thereof
CN116102677A
Hydrophobic association thick oil emulsion viscosity reducer for oil displacement as well as preparation method and application of hydrophobic association thick oil emulsion viscosity reducer
CN118108906A
Self-thickening gelled acid thickening agent and preparation method thereof
CN118812792A